Description of pathogenic bacteria in patients with respiratory symptoms associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Colombia (2023)
Viral respiratory infections may predispose to co-infections with other pathogenic microorganisms. In this study, pathogenic respiratory bacteria were detected using commercial kit Allplex™ Respiratory Panel 4 from nasopharyngeal samples from individuals suffering respiratory symptoms with and without severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Patients without respiratory symptoms were included as controls. Haemophilus influenzae and Streptococcus pneumoniae were detected from 12 patients (6%) in both, patients with respiratory symptoms (including hospitalized) (n?=?6) and individual without symptoms (n?=?6). Pathogenic bacteria possibly proliferate due to the limited immune response of patients with SARS-CoV-2, perhaps due to dysbiosis generated by the viral infection.